Kewenangan Pengadilan Dalam Penyelesaian Sengketa Perbedaan Hukum Waris - Muhammad Lutfi Syarifuddin (Hikamatzu | Journal of Multidisciplinary, 2025)
When a person dies, rights and obligations are not simply transferred but are instead transferred to others, especially their family (heirs). To ensure that the process of transferring these rights and obligations proceeds smoothly and orderly to the rightful recipients, namely the surviving heirs, it is necessary to regulate them through specific regulations (laws). However, not all rights and obligations of the deceased (heir) can be transferred to their heirs; only certain temporal matters can be transferred to their heirs. Therefore, inheritance law, in general, is the law that governs the process of transferring the rights and obligations regarding the assets of a deceased person (heir) to their family (heirs) or other surviving individuals. If there are two choices, some heirs want Islamic law, while other heirs want Civil inheritance law or Customary inheritance law, for those who want Islamic law can submit to the Religious Court and others can submit to the General Court, if this happens then it can cause difficulties for example if at the first or second hearing in the Religious Court the defendant is absent without a valid reason, so that the defendant is granted with a default decision. If each party requests execution it will encounter a very complicated path, this problem can only be resolved if one party files a judicial review (PK) to the Supreme Court, because the Supreme Court is the one who has the right to adjudicate cases that have permanent legal force